REFORMASI BIROKRASI PENYELENGGARAAN PELAYANAN KTP DI KABUPATEN PAKPAK BHARAT - Mukti Ali Brutu (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
ID card, within public administration context, has a lot of functions such as for applying for a job, proposing a loan to a bank, getting licenses, participating in a local vote, and so on. It has become a common administrative requirement for the people to obtain their civic rights. Of course, local government has the responsibility to provide ID card service for the people. Furthermore, the service delivery should always be improved to reach a state of demographic administrative order. In fact, a number of cases show that ID card service quality is still low, including that of Pakpak Bharat district. This article tries to provide recommendations for solving the problem.